Expanding Culturomics from Gut to Extreme Environmental Settings - Utkarsh Sood; Roshan Kumar; Princy Hira (mSystems, 2021)
ABSTRACT With the advent of metagenomics, a quest began to identify the dynamics of the microbial communities in different ecological niches. Altogether, this has resulted in identification of microorganisms but is limited to only a small number of phylogenetic groups that can be easily cultured. The majority of metagenomic sequencing data remains unassigned to any known microbial group and is regarded as the “microbial dark matter.” Our group is now working on integrating culturomics (isolation of pure cultures) and metagenomics from extreme environments, particularly from hot water springs and chemically contaminated soils. Our target is to culture the rare extremophiles with biotechnological significance by designing culture media based on inputs from metagenomics. While culturomics integrated with metagenomics has been extensively employed for updating the microbial catalog from the human gut, there is a need to extend this approach to extreme environmental settings to explore the microbial dark matter.